The Effects of Global Commodity Prices on Domestic Prices in Saudi Arabia - Moayad Al Rasasi; Goblan Algahtani; Abdulrahman Alqahtani (International Journal of Economics and Financial Issues, 2017)
This paper evaluates the impacts of global commodity prices on domestic prices in Saudi Arabia with aid of econometric techniques and monthly data over the period 2000:01-2016:09. We find evidence suggesting the influential role of global commodity prices on Saudi domestic prices over long run. In particular, we find that non-fuel commodity prices have more impacts on domestic prices than energy prices. Likewise, we find evidence, based on Granger causality analysis, suggesting that global commodity prices are useful indicators in capturing the movements in domestic prices.